Combination of chest compressions and interposed abdominal compressions in a swine model of ventricular fibrillation - Georgiou, Marios; Papathanassoglou, Elizabeth; Middleton, Nicos; Papalois, Apostolos; Xanthos, Theodoros (My University, 2016)
Purpose.The aim of this study was to investigate the effects of the combination of chest compressions and interposed abdominal compressions (IAC-CPR) in a swine model of ventricular fibrillation (VF).Methods Twenty healthy female Landrace-Large White pigs were the study subjects. At the end of the eighth minute of VF, animals in the control group (Group A) received chest compressions at a rate of 100/min, while animals in the experimental group received chest compressions and simultaneous interposed abdominal compressions (CC-IAC – Group B), both at a rate of 100/min. The primary end point of the experiment was return of spontaneous circulation (ROSC). Secondary outcomes were 48-h survival rate and 48-h neurologic outcome.Results.Six animals (60%) from Group A and 9 animals (90%) from Group B achieved ROSC (P = .121). There was a statistically significant difference in systolic aortic pressure, mean aortic pressure, right atrial pressures, and end-tidal carbon dioxide (ETCO2) between the two groups during the first cycle of CPR, while during the second cycle, diastolic aortic pressure was significantly higher in Group B. Coronary perfusion pressure (CPP) values in group B were significantly higher compared with those in Group A during the first and second cycle of CPR. Neurologic examination was statistically significantly better in Group B (75.00 ± 10.00 vs. 90.00 ± 10.00, P = .037).Conclusion ROSC did not differ statistically significant in the IAC-CPR compared to the CPR group only, while CPP was significantly higher in IAC-CPR–treated animals.
Keywords: Chest compressions; Swine model